PENERAPAN SIMPLE ADDITIVE WEIGTHING PEMILIHAN KAYU UNTUK PEMBUATAN GITAR - Putri Taqwa Prasetyaningrum; Rias Ilham Agung Nugroho (JUSIM (Jurnal Sistem Informasi Musirawas), 2020)
Wood is the main material for making guitars, if the wood selected is not suitable, then the guitars produced may not be perfect wood selection is not yet optimal if it only relies on one criterion, there must be a systematic and accurate calculation when selecting wood in order that the guitar produced can be perfect, when the guitar was sold, there would be no more complaints about it, such as inferior sound, fragile body, etc. One of the means to assist calculation is the Simple Additive Weighting (SAW) method,which can calculation the value of wood, criteria of wood, and value of each sub-criteria of wood, so that the wood chosen after the calculation would be suitable for marketing. After going through the stages of wood data testing from’fajar musik’, and the calculation also used predetermined criteria, namely sound quality, wood age, wood physique, and wood texture/pattern. Keywords - guitar, wood, selection decision support, simple additive weighting